1997
DOI: 10.1097/00000372-199702000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangioma-like Variant of Kaposi's Sarcoma: Clinicopathologic Study of Seven Cases with Review of the Literature

Abstract: The clinical and pathological features of seven cases of lymphangioma-like Kaposi's sarcoma (KS) are reported. As with the other subtypes of KS, the lymphangioma-like variant occurs more often in men aged 59-80 years. Clinically, the lesion appears intermingled with the classical forms of KS, but a "bulla-like" appearance recognized in seven of 13 cases has been considered as a clinical hallmark of this variant. Although occasional cases have shown aggressive behavior, the most frequent clinical course is slow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 17 publications
2
42
0
5
Order By: Relevance
“…Dermal edema and enlarged lymphatic vessels are prominent in bullous KS cases, and fibrosis can be observed in those patients who receive radiotherapy [8-13]. In our study, hyperkeratosis was observed in all bullous KS cases, and ulceration was detected in two cases.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Dermal edema and enlarged lymphatic vessels are prominent in bullous KS cases, and fibrosis can be observed in those patients who receive radiotherapy [8-13]. In our study, hyperkeratosis was observed in all bullous KS cases, and ulceration was detected in two cases.…”
Section: Discussionsupporting
confidence: 53%
“…To date, 30 reported cases with different terminologies have been available (Table 3) [5-21]. Cossu et al reported bullous KS frequency at 4% in epidemic KS cases [13]. Notwithstanding, in our series composed of classic KS cases, vesiculobullous changes were observed in 14% of all patients, whereas only 2% of these met the diagnostic criteria of bullous KS.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…1 The following criteria were suggested: (1) uniformly tan cribriform macular pigmentation in a zosteriform distribution; (2) a histologic pattern that consisted of a mild increase in melanin pigment in the basal cell layer and complete absence of nevus cells; (3) no history of rash, injury, or inflammation to suggest postinflammatory hyperpigmentation; (4) onset well after birth with gradual extension -age at onset was in the second decade of life in every case; and (5) lack of other associated cutaneous or internal abnormalities. 1 The following criteria were suggested: (1) uniformly tan cribriform macular pigmentation in a zosteriform distribution; (2) a histologic pattern that consisted of a mild increase in melanin pigment in the basal cell layer and complete absence of nevus cells; (3) no history of rash, injury, or inflammation to suggest postinflammatory hyperpigmentation; (4) onset well after birth with gradual extension -age at onset was in the second decade of life in every case; and (5) lack of other associated cutaneous or internal abnormalities.…”
Section: Progressive Cribriform and Zosteriform Hyperpigmentation -Thmentioning
confidence: 99%
“…Occasionally, there are associated systemic abnormalities. 1,2 The bullous lesion has been considered as a variant of a KS plaque, while an association with alterations in lymphatic drainage 7 and chronic lymphoedema 5 has been suggested. The linear nature of the pigmented bands probably reflects the clonal migration and proliferation of embryonic melanocyte precursors (melanoblasts).…”
Section: Progressive Cribriform and Zosteriform Hyperpigmentation -Thmentioning
confidence: 99%